Aplikasi Media Pembelajaran Alat Musik Gitar Berbasis Android Menggunakan Metode SDLC : indonesia - Rio Saputra; Dani Ahmadi; Ryan Prastiyo; Rizky Hermawan; Andry Maulana (Computer Science (CO-SCIENCE), 2022)
Nowadays, people's interest in playing the guitar is increasing. Playing the guitar can further enhance personal branding in today's digital era, many of the general public are suddenly famous for playing musical instruments such as the guitar. However, the ability to learn guitar instruments has constraints such as time and funds that are not small to attend guitar school, so many people choose to self-taught independently. However, self-study is not easy. Therefore, the author tries to do a study with the aim of making an Android-Based Guitar Musical Instrument Learning Media Application as an alternative way of learning guitar independently that can be used independently so that it can be used anywhere and anytime. By applying the SDLC (System Development Life Cycle) method, which is a method that describes the information system development life cycle. So that the application is divided into several levels that are tailored to the user. At each level there is material in the form of learning videos that can be listened to for an explanation. Based on the results of the Black Box testing carried out, the application that was built is functioning well, the input and output results are according to the results of the application. So the author can conclude that the Android-Based Guitar Musical Instrument Learning Media Application is very helpful for someone to learn guitar independently and effectively without having to spend money to attend music school.